Soil and Nigerian Food Security - Adepetu, J. A. (Obafemi Awolowo University Press, 2013)
Soil is the most important factor in agricultural production: its function as the medium for plant growth underscores this importance. At any location suitable for plant growth, the yield of crops, even varieties with the most high yielding potentials, depend on soil quality and soil management practices applied to cultivating the crop. For this reason, we must regard soil as our resource base for a, sustainable future. Among natural resources, soils are exceedingly responsive to human influence. With careful management we can improve their properties and productive potentials. But much more easily, soils can be destroyed and rendered less productive by misuse and thoughtless development.